Sociology of knowledge оn the generations formation mechanism - V. M. Pashinskiy (Социологический журнал, 2013)
Socialization process involves interaction between two generations – prevalent and growing one. The present article demonstrates, that different generations display two various types of rational behavior in terms of intergenerational relations – primarily instrumentally rational and value-rational one, respectively. This difference becomes the reason of misunderstanding between different generations and has got quite a wide range of consequences for development of human culture in general.